2019
DOI: 10.1002/adsc.201901398
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Intramolecular Mizoroki‐Heck‐Type Reaction of Diarylmethyl Carbonates

Abstract: A palladium-catalyzed intramolecular Mizoroki-Heck-type reaction of diarylmethyl tertbutyl carbonates has been developed. The reaction proceeds under external base-free, neutral conditions to form the corresponding methyleneindanes in good yields only with liberation of CO 2 and tBuOH. The resulting exo-methylene moiety is reactive and thus a good synthetic handle for further manipulations. Additionally, the asymmetric synthesis is also possible through a Pd/chiral Mandyphos ligand-mediated kinetic resolution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Miura and Hirano utilized diarylmethyl tert ‐butyl carbonates as secondary benzyl electrophiles to develop an intramolecular enantioselective Heck reaction of simple olefins, in which a kinetic resolution process was involved (Scheme 47). [ 59 ] The reaction in the presence of Pd/chiral Mandyphos ligand L27 proceeded efficiently under external base‐free conditions, affording the corresponding methyleneindane products in good yields with moderate to good enantioselecitvities. It is worth noting that this is a rare example of enantioselective Heck reaction of secondary benzyl electrophiles.…”
Section: Palladium‐catalyzed Intramolecular Asymmetric Heck Reactionsmentioning
confidence: 99%
“…Miura and Hirano utilized diarylmethyl tert ‐butyl carbonates as secondary benzyl electrophiles to develop an intramolecular enantioselective Heck reaction of simple olefins, in which a kinetic resolution process was involved (Scheme 47). [ 59 ] The reaction in the presence of Pd/chiral Mandyphos ligand L27 proceeded efficiently under external base‐free conditions, affording the corresponding methyleneindane products in good yields with moderate to good enantioselecitvities. It is worth noting that this is a rare example of enantioselective Heck reaction of secondary benzyl electrophiles.…”
Section: Palladium‐catalyzed Intramolecular Asymmetric Heck Reactionsmentioning
confidence: 99%
“…[48] Cyanoselenylation via a similar pathway was also reported to access selenoenol ethers. [49] Matsude et al [50] recently demonstrated a cascade cyclization of optically active 1,1-diarylmethylcarbonates 199 via Mizoroki-Heck followed by Suzuki coupling to furnish trans-1,2disubstituted indanes 200 (Scheme 30). [50a] The oxidative addition of Pd 0 to carbonate 199 established an equilibrium between η 1 /η 3 -benzyl Pd species 199 a/199 b. Intramolecular olefin insertion followed by Suzuki coupling, generated 200 in good yields (46-99 %; 98-> 99 % es; > 20 : 1 dr).…”
Section: Electrophilic Activation/reductive Elimination Cà C Bond Formation Via Nucleopalladationmentioning
confidence: 99%
“…Recently, Miura and co-workers achieved a palladiumcatalyzed intramolecular Heck-type reaction of diarylmethyl carbonates 7 (Scheme 7). 19 A variety of substituted indane derivatives 8 were formed in good yields under basefree, neutral conditions with only release of CO 2 and t BuOH. Moreover, the asymmetric synthesis of indane products was feasible via a Pd/optically active Mandyphos ligandmediated kinetic resolution (Scheme 7, eq.…”
Section: Scheme 6 Ligand-free Palladium-catalyzed Intramolecular Heckmentioning
confidence: 99%